An Annotated Translation from Novel “Flipped” By Wendelin Van Draanen - Shintia Pramudyaningtyas Ortantina (UPT P2M Politeknik Negeri Malang, 2020)
The existence of translation has broadened people’s knowledge. People can gain information about other countries’ culture easily, especially by reading novels. However, in translation process, particularly in literary translation, translator may encounter some problems since translator must maintain the beauty of the source text in the target text. This research is aimed to find out what problems are encountered and how the problems are solved. In the process of translation of this novel, I encountered two main types of problems, namely problem in understanding and problem in transfer, but apparently, I also encountered problems both in understanding and transfer. The problems that I found were in the form of words, phrases, and clauses. There were some ways that I took to solve the problems, such as looking up online dictionaries, searching on websites, and asking my advisors. Moreover, to get a better understanding of the terms that I wanted to translate, I entered a keyword on Google and browse the image or watched the film which was adapted from this novel.